Cardiac arrest with vagal stimulation during intraoperative nerve monitoring. (1st February 2016) - Almquist, Martin; Thier, Mark; Salem, Farhad
Abstract: Background: Intraoperative neuromonitoring (IONM) is widely used during thyroid surgery. During both intermittent and continuous IONM stimulation of the vagus nerve is performed. This has previously been reported to be safe. Methods: We present our findings based on the case reports of 2 patients. Results: IONM of the recurrent laryngeal nerve (RLN), following the standards of the International Neuromonitoring Study Group, was conducted in 2 patients, one undergoing thyroid surgery and the second parathyroid surgery. In both cases, after dissection and stimulation of the vagus nerve on 1 mAmp, the patients became asystolic. Resuscitation efforts were successful in both patients. Conclusion: These 2 cases demonstrate that stimulation of the vagus nerve during IONM can lead to profound cardiac events. Consideration should be given to these potential complications when utilizing IONM. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2419–E2420, 2016